The Impact of Digital Health Technology on Improving Healthcare Access and Effectiveness - Wijayanti, Rima Rizqi; Makmun, Kartika Sari (Public Health and Safety International Journal, 2024)
Digital health technologies, including telemedicine, wearable devices, and Electronic Medical Records (EMR), have the potential to significantly enhance healthcare access and effectiveness. This research aims to analyze the impact of these technologies on improving healthcare systems, focusing on their benefits, challenges, and future prospects. The study found that digital health solutions, particularly telemedicine and mobile health applications, bridge geographical gaps and improve access to healthcare, especially for underserved populations. Moreover, EMRs streamline patient information management, and wearable devices offer real-time health monitoring, contributing to better healthcare efficiency. However, challenges such as data privacy concerns, digital literacy barriers, and the digital divide must be addressed to fully realize the potential of these technologies. The research suggests that efforts to improve digital literacy, strengthen data security measures, and ensure equitable access to digital health tools are essential for maximizing their benefits. Overall, digital health technologies offer great promise in transforming healthcare delivery and improving outcomes worldwide.